5x+1-4x=-4

Simple and best practice solution for 5x+1-4x=-4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5x+1-4x=-4 equation:


Simplifying
5x + 1 + -4x = -4

Reorder the terms:
1 + 5x + -4x = -4

Combine like terms: 5x + -4x = 1x
1 + 1x = -4

Solving
1 + 1x = -4

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1' to each side of the equation.
1 + -1 + 1x = -4 + -1

Combine like terms: 1 + -1 = 0
0 + 1x = -4 + -1
1x = -4 + -1

Combine like terms: -4 + -1 = -5
1x = -5

Divide each side by '1'.
x = -5

Simplifying
x = -5

See similar equations:

| 2x+5-1=6 | | -5*s-13=-68 | | x-25=-9 | | -94x-76=-94-23x | | 4x=5+3.8*x | | 3(x+4)+1=31 | | 0.15(x+50)-0.04(x-20)=2.8 | | -6g+3(-7+4g)=1-g | | 2.5x+9=209+.5x | | 6w+48=48 | | -20=-4-(6x) | | y=-2/3(-1)+1 | | y=-2/3(1)+1 | | 2u=-8 | | z-0.5=0.25z-0.125 | | U-9.9=4.99 | | y=-2/3(0)+1 | | 9(4x+8)=12(12+3x) | | h=-16t^2+1000 | | 32=6(x+4)-8x | | (3x+4)+(2x+2)= | | 8+5(7+5n)=193 | | 2.5x+1.96=1.7x+2.92 | | w+6-13=-27 | | 3(5x+4)=31 | | 3x+2(5)=0.2(2y+1) | | 45+5.50x=195+4.25x | | -x+3(-x+8)=0 | | 3+4+a=12 | | (C+5)+(c-1)=90 | | 4y+6(y+8)= | | 3(x+1)+4x=24 |

Equations solver categories